Determination of lead and cadmium in fresh bovine meat - Ζαντόπουλος, Ν.; Τζέκος, Α.; Αντωνίου, Β.; Τσούκαλη - Παπαδοπούλου, Ε.; Ναθαναήλ, Β.; Στοΐλης, Ε.; Καλαμπούκας, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
No abstract (available).